Betydelsen av skogsbruksplaner som verktyg vid anskaffning av virke - Harrysson, Johan (SLU/School for Forest Management, 2009)
Forest management plans have been sold to private forest owners by wood supplying companies for a long time. These plans are considered to be effi-cient tools to identify measures and wood volumes, and are simply a starting point for discussions between private forest owners and round wood pur-chasers. However, large variations are observed between different purchas-ers, in their usage of the plans. The purpose of this report is to identify to what extent a forest management plan can promote an increase in the amount of wood which a round wood purchaser can obtain and to find differences in the way of using the plans between different wood purchasers. Furthermore, the purpose is also to ana-lyse if varying owner structures can be underlie variations in the selling of forest management plans. Qualitative interviews with nine of Stora Enso’s round wood purchasers were performed. The interviews was recorded and put together in a docum-ent for further analysis. The conclusion of the interviews is that forest management plans has been and will continue to be a powerful tool in wood supplying business. It is however, important that the development do not stagnate and that the re-search must continue to meet the demands from future private forest owners. The result in the report shows that private forest owners who have bought forest management plans from Stora Enso are generally considered to be a stable and important group of wood suppliers. The goal should thus be to increase the amount of private forest owners who has a forest management plan. Keywords: Forest management plan, wood supply